Collaborative planning of ambitious Mathematics teaching practices: teachers' reflections on animations and simulations in exploratory teaching - João Carlos Alves Pereira Junior; Everton José Goldoni Estevam (Universidade Cruzeiro do Sul, Ensino de Ciências e Matemática, 2022)
This article discusses actions and reflections of two Mathematics teachers when planning, in a collaborative way and mediated by a researcher, teaching practices considered ambitious, involving Exploratory Mathematics Teaching and animations and simulations in the GeoGebra software. We seek to understand what these teachers consider and what they mobilize or develop in this process. This is an intervention study, whose data derive from interviews and practice planning meetings, which constitute two units of analysis that focus, respectively, on highlighted aspects and aspects developed or mobilized by the teachers. Thus, expectations, beliefs and conceptions of teachers are evidenced, as well as actions and reflections oriented towards the integration of technology, which were enhanced by the assumed teaching perspective. It is concluded, therefore, that collaborative planning constitutes good opportunities for investigation and understanding of teacher professional development, and that Mathematics TPACK associated with Instrumental Genesis constitute relevant contributions to studies of this nature.